Penentuan Arah Kiblat Menggunakan Kompas Easy Qiblat 3 In 1 Pada Handphone Android ( Study Penelitian di Masjid An Nur Pare Kediri) - Sapri Ali; Muhammad Ansori (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
The problem is the variety of tools used in determining the Qibla direction, both classical and modern, for example using a special stick, Global Qibla Rashdul, local Qibla rashdul, theodolite, miqyas, rubu 'mujayyab, theodolite, GPS (Global Positioning System) and others. So that the figures of astronomy sometimes differ in terms of determining the direction of the Qibla. The more sophisticated these tools, the higher the azimuth data accuracy will be. With the development of time found a tool that shows the direction of the wind called a compass. The compass is made of a magnetic needle which consists of two poles, namely the north and south poles and is equipped with a protractor, so that this compass pointing tool is very useful for Muslims and can determine the Qibla direction. Even with the development of the compass era, you can also use Android phones, one of which is using the Easy Qibla 3 In 1 Compass. From the description above, the author is interested in discussing more deeply about the 3 in 1 easy qibla compass which has its strengths and weaknesses. In this study, the issue discussed is how is the level of accuracy in determining the Qibla direction using an easy Qibla 3 in 1 compass on an Android phone? What are the advantages and disadvantages of each Qibla direction determination using an easy Qibla 3 in 1 compass on an Android phone? The type of research used by this author is classified as field research using qualitative, descriptive (descriptive approach) methods, which aims to better understand the 3 in 1 easy qibla compass on mobile phones in terms of weaknesses and strengths. where the primary data is data obtained directly from the results of observations, kompas easy qiblat 3 in 1. The secondary data are all documents in the form of books, writings, journals, papers related to the object of research. The findings from this research are that when the practice of measuring the Qibla is not the same, there is a difference of about 0˚ 8′ 52.42ʺ which if made in meters from the east to west line distance which is both 9 meters produces a difference of about 0.03 meters . According to the author, this is still within reasonable limits or allowed deviation categories. maybe this is due in part to the advantages and disadvantages of the tool. The advantages of the Easy Qibla 3 in 1 compass, such as how to use it is relatively easy, still functions in all kinds of weather and conditions, easy to use for ordinary people or not especially astronomers, easy to carry everywhere. While the drawbacks, such as being prone to electric current flowing in the conducting cable, electronic objects that contain magnets, for example: speakers, televisions, radios, telephones, and others, and are also prone to buildings that contain a lot of metal objects.